VIDEO TO IMPROVE STUDENTS’ SPEAKING ABILITY - Dian Anik Cahyani (Faculty of Culture, Management, and Business Universitas Pendidikan Mandalika (UNDIKMA), 2015)
Video as an audio-visual material in teaching English has grown rapidly and it is obvious that the use of video is a great help for students in stimulating and facilitating the target language. This study tries to solve students’ speaking problems and improve speaking ability by using video. The writer uses Classroom Action Research as research design. The implementation of video in teaching speaking class is arranged to bring benefit of the language learners. Video can make the classroom atmosphere more interesting and make students easier to speak. Video also stimulates students to be active. The students’ response about the implementation of video is positive and it will be alternative strategy in teaching speaking. So, video can improve the students’ speaking ability.